SOME IDEAS ON THE ROCK CYCLE: 1788-1988 - Gregor B. (My University, 1992)
Hutton's procrastination on the subject of unconformities left his cyclic vision of geology in the shadows, while his success in demonstrating the igneous origin of granite led on to Classical Magmatism, a paradigm of secular evolution that reigned practically unchallenged for almost a century. When radiometric dating revealed the true extent of geologic time, a neo-Huttonian, cyclic view gained strength in Europe because of its ability to explain the salt content of the ocean and the sodium fixed in metamorphism of sediments to paragneiss, both of which had become embarrassing to the magmatists. Meantime, in North America, a quite independent movement was afoot to claim for sediments and cyclic processes their rightful place in geologic theory. It led to the acknowledgment that the cyclic and secular views of the Earth are complementary and not contradictory, and that geologic materials are recycled on varying time scales against a background of slow, secular evolution of the Earth.